Characterization of Plant-Based Natural Fiber Ropes for Potential Futuristic Application as Reinforcement in Concrete Structures - Ebisa T. Daba; Daniel H. Zelleke; Vasant A. Matsagar; Shashank Bishnoi; Venkateshkumar R. Kodur (Journal of Natural Fibers)
The utilization of plant-based natural fibers (PNFs) in concrete is gaining considerable attention owing to their potential applications in developing sustainable concrete structures. However, the characteristics of PNF ropes for their possible use as eco-friendly reinforcement have not been extensively studied. Also, there is inadequate research on performance enhancement of the PNF ropes. Thus, this research focuses on the characterization of various PNF ropes and explores methods of enhancing their performance. Herein, jute, nettle, coir, sisal, and cotton fiber ropes are subjected to alkali and hydrothermal treatments, after which the effects of the treatments on the morphology, chemical, physical, mechanical, and thermal characteristics of the ropes are experimentally investigated. The findings of field emission scanning electron microscopy and energy-dispersive X-ray spectroscope analyses show that alkali and hydrothermal treatments remove impurities and hydrophilic components from the surface of PNFs. These findings are confirmed by the reduction in the water absorption capacity of the ropes after the treatments. Furthermore, the results demonstrate that surface roughness, ultimate tensile strength, and thermal stability of most of the ropes increase upon the treatments. Overall, jute fiber ropes exhibit the highest tensile strength before and after the treatments, making them the most promising for reinforcement applications.